2002
DOI: 10.1093/jnci/94.11.858
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Heterozygosity in Benign Breast Epithelium in Relation to Breast Cancer Risk

Abstract: The multistage model of breast carcinogenesis suggests that errors in DNA replication and repair generate diversity in the breast epithelium (the mutator phenotype), resulting in selection and expansion of premalignant clones with an acquired survival advantage. We measured loss of heterozygosity (LOH) in breast epithelial cells obtained by random fine-needle aspiration (FNA) biopsy from 30 asymptomatic women whose risk of breast cancer had been defined by the Gail model. Polymorphic microsatellite markers wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 15 publications
0
36
0
1
Order By: Relevance
“…These findings were confirmed using qRT-PCR, validated in an independent set of 24 case samples, and compared to rFNA samples from 12 healthy controls. This report on a total of 66 women is larger than other studies of molecular features of normal breast epithelium, where total sample size has generally been under 50 women (23). Thus, our present findings based on 54 cases and 12 healthy controls constitute one of the largest of these challenging studies.…”
Section: Introductionmentioning
confidence: 66%
“…These findings were confirmed using qRT-PCR, validated in an independent set of 24 case samples, and compared to rFNA samples from 12 healthy controls. This report on a total of 66 women is larger than other studies of molecular features of normal breast epithelium, where total sample size has generally been under 50 women (23). Thus, our present findings based on 54 cases and 12 healthy controls constitute one of the largest of these challenging studies.…”
Section: Introductionmentioning
confidence: 66%
“…This finding parallels our previous studies in tumors of the prostate and their matched TA-HN tissues, 28 and is in agreement with the work of previous investigators who reported that genetic alterations, including telomere attrition and loss of heterozygosity, occur in histologically normal tissues adjacent to breast tumors. [34][35][36][37][38][41][42][43][44] In these previous studies, the sites of telomere attrition, loss of heterozygosity, and AI were physically distant from one another and from the tumors, albeit in most cases at undefined distances from the corresponding tumor lesions. 24,[42][43][44] In contrast, and to our knowledge, the findings in cohort 1 represent the first study in breast cancers that analyzes genomic instability at defined distances (1 cm and 5 cm) from the visible tumor margins.…”
Section: Discussionmentioning
confidence: 89%
“…[34][35][36][37][38][41][42][43][44] In these previous studies, the sites of telomere attrition, loss of heterozygosity, and AI were physically distant from one another and from the tumors, albeit in most cases at undefined distances from the corresponding tumor lesions. 24,[42][43][44] In contrast, and to our knowledge, the findings in cohort 1 represent the first study in breast cancers that analyzes genomic instability at defined distances (1 cm and 5 cm) from the visible tumor margins. Consequently, this study reveals that genomic instability in tumor adjacent, histologically normal breast tissues is a function of distance from the tumor lesion, showing decreasing extent of genomic instability with increasing distance from the tumor margin.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…We cannot tell whether the ipsilateral subsequent events in this (14)) LOH 9p 3/6 (50)) 2/13 (15)) LOH 11p 0/6 (0)) 1/15 (7)) LOH 11q 1 5/6 (83)) 3/17 (18)) LOH 16q 2 5/11 (45) It was recently demonstrated that a higher proportion of LOH detected in benign breast epithelial cells correlated with an increased breast cancer risk [36]. The present LOH study, however, did not show that an overall increased frequency of LOH would indicate a higher risk of recurrences or new subsequent breast cancers, as allelic loss was more common in DCIS grade 1 than in DCIS grade 3.…”
Section: Discussionmentioning
confidence: 95%